PENGARUH GIRO WAJIB MINIMUM DAN DANA PIHAK KETIGA TERHADAP TINGKAT PEMBIAYAAN MUSYARAKAH PADA BANK MEGA SYARIAH - Randa, Noer Azizah; Darmawati, Darmawati; Rahmatullah, Nur (Indonesian Scientific Journal of Islamic Finance, 2025)
This study examines the impact of Minimum Statutory Reserves (Giro Wajib Minimum/GWM) and Third-Party Funds (Dana Pihak Ketiga/DPK) on musyarakah financing at Bank Mega Syariah from 2017 to 2022. Motivated by internal and external factors influencing musyarakah financing, the research adopts a quantitative explanatory approach using multiple linear regression analysis. Data were sourced from the bank’s financial reports, and classical assumption tests—normality, multicollinearity, heteroscedasticity, and autocorrelation—were conducted to ensure model validity. The results show that GWM significantly affects musyarakah financing partially, with a significance level of 0.017. Similarly, DPK has a significant partial effect, with a significance level of 0.000. Both variables also have a simultaneous significant effect. These findings suggest that effective GWM management can improve liquidity and financing performance without violating liquidity requirements. Moreover, enhancing DPK through innovative Sharia-compliant savings products can stimulate financing growth. In conclusion, GWM and DPK are crucial in shaping musyarakah financing performance. Policy recommendations include optimizing liquidity strategies, innovating DPK mobilization aligned with Sharia principles, improving liquidity risk management, and increasing public education about Islamic finance to foster sustainable development in the Islamic banking sector.